Thai Computer Studies Student Teacher Complex Problem-Solving Skills Development: A Cooperative Learning Management Model - Natchanun Sermsri; Aukkapong Sukkamart; Thiyaporn Kantathanawat (Journal of Higher Education Theory and Practice, 2022)
The research aim was to develop cooperative learning management (CLM) model using computational thinking (CT) and mind mapping techniques to promote Thai computer studies student-teacher (CSST) complex problem-solving skills (CPSS). The sample was 15 first-year CSSTs in the Faculty of Education's Computer Studies Department of Thailand's Thonburi Rajabhat University. The pre-study achievement test classified students into three levels (weak, moderate, or strong). Five experts were involved in the assessment of the CLM plan, which was determined to have a content validity index (CVI) at the highest level (mean = 4.00). They also evaluated the 21 indicator rubric scoring-type test tool for complex problem-solving skills (CPSS) and determined its CVI mean = 3.99. After a pilot test of 30 student teachers, a 42-item questionnaire was finalized. The final CPSS course involved five primary components within an eight-step process. The CSST used six sessions of four hours each. Results showed that the final course post-test score was 90.40 for all 15 student-teachers, significantly higher than the 70% achievement level setting.
Keywords: Education and Critical Thinking Development; Innovative Teaching and Learning Methods; Learning Styles and Cognitive Differences